Impact on Adherence and Clinical Outcomes of an Anticoagulation Stewardship Program in Users of Direct Oral Anticoagulants - Mayra A. Arenas-Beltrán; Paula Ruiz-Talero; Karen Navarro-Pérez; Pilar Alarcón-Robles; Alice Daniela Salamanca; Oscar Muñoz (Revista de Investigación Clínica)
Background: Anticoagulation stewardship in warfarin users reduces thromboembolic and bleeding events and improves adherence. Limited data exist on its impact on adherence among direct oral anticoagulants (DOACs) users. Objective: To evaluate whether inpatient and outpatient follow-up in an anticoagulation stewardship program improves adherence and clinical outcomes in DOAC users compared to usual care. Methods: Cohort study of patients initiating DOAC therapy at a university medical center. Participants were categorized into anticoagulation stewardship and usual care cohorts. Adherence was assessed at 30, 90, and 180 days. Univariate and multivariate logistic regression models were used to identify factors associated with lower adherence. Results: 250 patients were included, with 81 receiving anticoagulation stewardship follow up. Adherence at 30 days was intermediate-high in over 90% of participants. The no-follow-up group showed a higher proportion of patients with low adherence (9.4% versus 2.4%, p = 0.003) and bleeding complications (4.1% versus 0%, p = 0.063). Anticoagulation stewardship exhibited a trend toward higher adherence (odds ratio [OR]: 3.51; 95% confidence interval [CI]: 0.74–16.47; p = 0.107). Factors associated with lower adherence included higher educational level (OR: 0.20; 95% CI: 0.05-0.75; p = 0.018), enrollment in a subsidized health system (OR: 0.08; 95% CI: 0.01-0.64; p = 0.018), and deep venous thrombosis as an indication for anticoagulation. Conclusion: Anticoagulation stewardship programs may enhance adherence to DOAC therapy. Prospective studies are needed to confirm these findings.